To factor the polynomial \(2x^5 - 4x^3 + 2x\), we can start by factoring out the common term.
The common factor in each term is \(2x\):
\[ 2x^5 - 4x^3 + 2x = 2x(x^4 - 2x^2 + 1) \]
Now, we need to factor the quadratic-like expression \(x^4 - 2x^2 + 1\). We can make a substitution \(y = x^2\), which transforms it into:
\[ y^2 - 2y + 1 = (y - 1)^2 \]
Replacing \(y\) back, we have:
\[ (x^2 - 1)^2 \]
The expression \(x^2 - 1\) can be further factored as it is a difference of squares:
\[ x^2 - 1 = (x - 1)(x + 1) \]
So we can write:
\[ (x^2 - 1)^2 = [(x - 1)(x + 1)]^2 = (x - 1)^2(x + 1)^2 \]
Putting it all together, we factor the original polynomial:
\[ 2x^5 - 4x^3 + 2x = 2x(x - 1)^2(x + 1)^2 \]
Next, we can solve the equation \(2x^5 - 4x^3 + 2x = 0\):
Setting the factored form equal to zero:
\[ 2x(x - 1)^2(x + 1)^2 = 0 \]
This gives us the solutions:
- \(2x = 0 \Rightarrow x = 0\)
- \((x - 1)^2 = 0 \Rightarrow x = 1\) (with multiplicity 2)
- \((x + 1)^2 = 0 \Rightarrow x = -1\) (with multiplicity 2)
The unique solutions are:
- \(x = 0\)
- \(x = 1\)
- \(x = -1\)
Thus, the answer from your options for the unique solutions is:
C. \(x = 0, x = 1\)